Tunneling current noise in the fractional quantum Hall effect: when the effective charge is not what it appears to be - Snizhko, Kyrylo (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Fractional quantum Hall quasiparticles are famous for having fractional electric charge. Recent experiments report that the quasiparticle’s effective electric charge determined through tunneling current noise measurements can depend on the system parameters such as temperature or bias voltage. Several works proposed to understand this as a signature for edge theory properties changing with energy scale. I consider two of such experiments and show that in one of them the apparent dependence of the electric charge on a system parameter is likely to be an artefact of experimental data analysis. Conversely, in the second experiment the dependence cannot be explained in such a way.